Parianella (Poaceae, Bambusoideae): morphological and biogeographical information reveals a new genus of herbaceous bamboos from Brazil - Ferreira, Fabrício Moreira; van Den Berg, Cássio; Hollowell, Victoria C.; Oliveira, Reyjane Patrícia (Phytotaxa, 2013)
Differences in the inflorescence morphology and geographical distribution indicate that two species found in the Atlantic Rain Forest of southern Bahia, Brazil, do not belong to Pariana, a genus of herbaceous bamboos (tribe Olyreae, Poaceae) where they were previously classified. We describe a new genus, Parianella, in order to accommodate these two species. Their taxonomic affinities within subtribe Parianinae are discussed, and a key for identification of genera in this group is presented.